2009
DOI: 10.1521/jaap.2009.37.2.353
|View full text |Cite
|
Sign up to set email alerts
|

Delineating Prototypes of Training Psychotherapy

Abstract: There is no reported research comparing psychotherapy for trainees to psychotherapy for clinical patients. This preliminary study examines similarities and differences between the Training Psychotherapy Experience (TPE), an elective offered to residents in a large psychiatry training program, and psychotherapy conducted by the same clinicians in their private practices (TAU). We used the Psychotherapy Process Q-set (PQS; Ablon & Jones, 1988; Ablon, Levy, & Katzenstein, 2006). All program consultants who perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
2
0
0
Order By: Relevance
“…Of these 69 prospective participants, 49% went on to complete the study, yielding a participant sample of 34 psychotherapists. This sample size is consistent with Q-methodology (prioritizing phenomenological subjectivity over generalizability; McKeown & Thomas, 1988;Watts & Stenner, 2012), and with other Q-method investigations of clinicians' perspectives (e.g., Lister & Gardner, 2006;Schottenbauer, Arnkoff, Glass, & Gray, 2006;Weis, Schottenbauer, & Gray, 2009). Indeed, a systematic review of recently published Q-methodological studies found an average participant sample size of N ϭ 40 (range ϭ 26 to 103; Dziopa & Ahern, 2011).…”
Section: Methods Participantssupporting
confidence: 83%
“…Of these 69 prospective participants, 49% went on to complete the study, yielding a participant sample of 34 psychotherapists. This sample size is consistent with Q-methodology (prioritizing phenomenological subjectivity over generalizability; McKeown & Thomas, 1988;Watts & Stenner, 2012), and with other Q-method investigations of clinicians' perspectives (e.g., Lister & Gardner, 2006;Schottenbauer, Arnkoff, Glass, & Gray, 2006;Weis, Schottenbauer, & Gray, 2009). Indeed, a systematic review of recently published Q-methodological studies found an average participant sample size of N ϭ 40 (range ϭ 26 to 103; Dziopa & Ahern, 2011).…”
Section: Methods Participantssupporting
confidence: 83%
“…It is important to note the preliminary and exploratory nature of our study. Generalisability is limited due to our small sample – although this is comparable to similar PQS studies (Schottenbauer et al., ; Weis, Schottenbauer & Gray, ). Our sample was also comprised of participants who were members of professional organisations – and perhaps more interested in research‐related activities than other community clinicians.…”
Section: Discussionsupporting
confidence: 53%